Impact of Leaflet Tethering on Residual Regurgitation in Patients With Degenerative Mitral Disease After Interventional Edge-to-Edge Repair - Ge, Zhenyi; Pan, Wenzhi; Li, Wei; Wei, Lai; Kong, Dehong; Pan, Cuizhen; Zhou, Daxin; Shu, Xianhong; Ge, Junbo (Frontiers in Cardiovascular Medicine, 2021)
Background: Grade 2+ residual mitral regurgitation (MR 2+) is associated with the recurrence of MR and a lower survival rate in interventional mitral valve edge-to-edge (EE) repair. We sought to determine the mitral valve (MV) anatomic factors affecting residual MR 2+ during interventional EE repair with the ValveClamp system in patients with degenerative MR (DMR). Methods: In this multicenter study, 62 patients with significant (grade 3+ to 4+) DMR underwent ValveClamp implantation across eight centers from July 2018 to December 2019. Patient clinical, anatomical, and procedural characteristics were prospectively collected and retrospectively analyzed. Results: A single clamp was implanted in 59 patients, and two clamps were implanted in three patients. Residual MR 2+ was found in 14 patients (22.6%) immediately after the ValveClamp procedure. Patients with residual MR 2+ showed significantly larger preoperative tenting sizes and annular dimensions than the residual MR ≤ 1+ group. Multivariate analysis identified tenting volume as the major determinant of residual MR 2+ after ValveClamp procedures (odds ratio [OR], 1.410 per 0.1 mL/m2 increase; 95% confidence interval [CI], 1.167–1.705; P < 0.001). Receiver operator characteristic curves identified a tenting volume index ≥ 0.82 mL/m2 as the optimal cut-off point to predict residual MR 2+ (area under curve, 0.84). Patients with a tenting volume index ≥ 0.82 mL/m2 were more likely to develop recurrent 3+ MR or undergo MV surgery during short-term follow-up (P < 0.001). Conclusions: Preoperative assessment of the tenting volume index will help to predict intraoperative residual MR 2+ in patients with DMR receiving EE-based interventional repair. Improvements in the interventional strategy are warranted for sustained MR reduction in patients with DMR with unfavorable anatomy.